VALIDITY OF ENGAGEMENT INSTRUMENT DURING ONLINE LEARNING IN MATHEMATICS EDUCATION - Hidayat, Riyan; Imami, Muh Khairul Wajedi; Liu, Sibo; Qudratuddarsi, Hilman; Mohd Saad, Mohd Rashid (LPPM Universitas Jambi, 2024)
The current study aimed to assess the validity of the engagement instrument during online learning in mathematics education. This study used a survey research design as its approach. The current research participants were 203 Generation Z students in West Nusa Tenggara Barat, Indonesia. Convenience sampling techniques were used to assess who had completed the online survey. Three procedures were used to analyze the data in this research: exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and Rasch analysis. EFA revealed that the online engagement instrument had two sub-components: behavioral engagement and emotional engagement. At the same time, the CFA results showed that the model fit indices established the first- and second-order model's two-factor structure. Finally, the results showed that the online engagement instrument’s item and person reliability were good. The findings indicate a potential for enhancement even though the Rasch analysis largely supported the results of EFA and CFA. The current research’s novelty is that it provides a valid and reliable instrument to assess student`s engagement during online learning in a mathematical education context. Using the current instrument can ensure the accuracy, reliability, and credibility of research on student engagement during online learning in mathematics education.